2015
DOI: 10.1371/journal.pone.0137518
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Source Case Investigation for Tuberculosis (TB) and HIV in the Caregivers and Household Contacts of Hospitalised Young Children Diagnosed with TB in South Africa: An Observational Study

Abstract: BackgroundContact tracing, to identify source cases with untreated tuberculosis (TB), is rarely performed in high disease burden settings when the index case is a young child with TB. As TB is strongly associated with HIV infection in these settings, we used source case investigation to determine the prevalence of undiagnosed TB and HIV in the caregivers and household contacts of hospitalised young children diagnosed with TB in South Africa.MethodsCaregivers and household contacts of 576 young children (age ≤7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
1
11
1
Order By: Relevance
“…As the majority of child TB is not bacteriologically confirmed, we garner important information by comparing NNS using all forms of TB as our outcome and demonstrate that the NNS was 40% greater for a child index case compared to an adult index case. Previously reported source case investigations including children hospitalized for TB in TB/HIV high burden settings have demonstrated 2–3% yield [22, 23]. Similarly, the yield of source case investigation originating from index cases under five years of age participating in our program was 2.5%.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…As the majority of child TB is not bacteriologically confirmed, we garner important information by comparing NNS using all forms of TB as our outcome and demonstrate that the NNS was 40% greater for a child index case compared to an adult index case. Previously reported source case investigations including children hospitalized for TB in TB/HIV high burden settings have demonstrated 2–3% yield [22, 23]. Similarly, the yield of source case investigation originating from index cases under five years of age participating in our program was 2.5%.…”
Section: Discussionsupporting
confidence: 50%
“…Although previous studies have demonstrated this potential [22], studies have also demonstrated significant challenges linking new cases to prompt treatment [29] and consistently low uptake of preventive TB treatment [3035]. Similarly, only 25% of eligible contacts evaluated by our program initiated IPT.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We also observed limited contact tracing, which is of added concern because data from Soweto, Johannesburg, have shown high rates of undiagnosed TB and HIV in the household contacts and caregivers of children with TB. [29]…”
Section: Researchmentioning
confidence: 99%
“…A similar study by [77] in a study by [76] out of 267 index TB cases screened, 27 (10%) were HIV cases which is consistent with the finding of 4.3%. Further study by [73] generated 63% of HIV cases, though greater than study findings of 4.3% but authenticates the influence of HIV on TB transmission. This implies that integrating TB/HIV strategy during contact tracing of index is strongly recommended.…”
Section: Discussionmentioning
confidence: 54%